Peran Bauran Pemasaran (Product, Price, Promotion, Place) dalam Meningkatkan Daya Saing MTsS Khazanah Kebajikan - Aolia Lavianis; Kamelia Azhar; Ghaida Diffa Syahida; Nur Azizah; Siskya Rahmat; Zahratul Munawwaroh (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2026)
This study aims to analyze the role of the marketing mix, consisting of product, price, promotion, and place, in enhancing the competitiveness of MTsS Khazanah Kebajikan. This study employed a descriptive qualitative approach with a case study design. Data were collected through in-depth interviews, observations, and documentation and analyzed using thematic analysis. The findings indicate that the product aspect is reflected in the differentiation of educational services, flagship programs, and extracurricular activities that provide added value to the institution. The price aspect is implemented through transparent and affordable tuition policies supported by scholarship programs. The promotion aspect is carried out through digital media, direct communication, and word-of-mouth marketing, which contribute to increasing student enrollment. Meanwhile, the place aspect is strengthened through the optimization of communication channels with parents and the development of the school's digital presence. Overall, the integration of these four elements contributes to strengthening the institution's image, increasing public trust, and enhancing the competitiveness of MTsS Khazanah Kebajikan amid the increasingly competitive educational environment.